Features Of Orthopedic Treatment For Complete Adentia - Djalolidinova Shakhlo Djamolidinovna (Genius Journals, 2024)
Many people do not even imagine what this dental disease is. But those who are faced with this experience what happened as a serious problem that significantly reduces the quality of life. Adentia – this term means the absence of teeth. Complete adentia means that a person has no teeth at all. There is not a single tooth in either the upper or lower row. Nowadays, traditional prostheses have not lost their popularity, although they are not a high-quality treatment for adentia. There are several types of such prostheses
Keywords: orthopedic treatment; complete adentia; prosthetics